Characterization of clinical indices of patients with tick-borne borreliosis in acute stage against the background of opisthorchosis invasion - S. A. Pershina; N. G. Zhoukova; L. V. Loukashova; I. N. Oudintseva (Бюллетень сибирской медицины, 2008)
Studied clinical aspects of a current of a sharp stage tick-borne borreliosis against opisthorchosis. On the basis of the conducted research an adverse current sharp tick-borne borreliosis, which is characterizing lengthening of the incubatory period, an encephalopathy with proof vegetative infringements and a long asthenic syndrome was established. All it as a whole leads to increase in duration of the period rehabilitations.